(untitled) (Docentes 2.0 Journal, 2023)
At present, the use of various information technologies has exceeded limits not seen before, promoting a restructuring based on its nature. The research aims to analyze the context of technologies based on artificial intelligence and its impact in the absence of legislative regulation in the country of Mexico within the teaching field. The research was based on the inductive method, humanist paradigm, topic narrative design, and exploratory documentary type with cross-section. For the research development, the Redalyc scientific information system, the SciELO repository, and the journal Institución de Investigaciones Jurídicas IIJ were considered, as well as the dissertation in development. The documentary research technique was applied, identifying electronic articles contained in the mentioned magazines. Subsequently, the results were identified by analyzing the content and theme to establish their consideration in the investigation. It was possible to observe that at the time present, there is not enough information on the subject. Therefore, it is necessary to consider the topic’s relevance within the educational environment.